Las fronteras de la lengua vasca a lo largo de la historia - Carlos, CID ABASOLO (Revista de Filología Románica, 2002)
Based on more or less reliable evidence, such as toponymy, the Basque language is supposed to have once been present in an area greater than its current territory, moving eastwards (until the Indo-European invasions) and westwards (until the arrival of the Romans). In the peninsular area, Basque was pushed back first by Latin and then by Spanish, and only did it regain part of its lost ground during the Reconquest of Spain, when the Basque-speaking population occupied lands in Northern Burgos and La Rioja. In the continental area, Basque has held its steady boundaries for the last 500 years. Nowadays, the situation has changed substantially: it seems there is no stopping the regression of Basque in the French zone. Whereas, the regression has stopped, or at least decreased, in the Basque Autonomous Community due to the so-called policy of linguistic normalization.